Integrating Pancasila in Character Education: A Qualitative Analysis of Ethical Values for Nation-Building - Farwati, Sizka; Iskhak, Muhamad; Nunu Mahnun (HEUTAGOGIA: Journal of Islamic Education, 2023)
This research delves into the critical role of Pancasila, the philosophical foundation of Indonesia, in shaping character education within the nation. Utilizing a qualitative descriptive methodology, predominantly through extensive literature reviews, the study investigates how Pancasila's core ethical values significantly influence character development. Emphasizing the integration of Pancasila's principles—Belief in the Divine, Just, and Civilized Humanity, Unity of Indonesia, Democracy led by the Wisdom of Deliberations among Representatives, and Social Justice for all Indonesians—this research underscores their essentiality in instilling moral and ethical consciousness in Indonesia's diverse populace. Key findings reveal the effectiveness of the threefold strategy of "star yourself, start small, starting from now" in embedding these values into character education. Despite modern challenges, the study highlights the transformative potential of Pancasila in fostering morally and ethically conscious citizens. The implications for educators and policymakers are profound, advocating for comprehensive and integrated character education strategies. This research contributes to the broader understanding of character education's pivotal role in promoting ethical development and fortifying Indonesia's unique cultural and philosophical identity.